Temperature memory effect in a magnetic shape memory alloy for monitoring of minor over-cooling. (15th January 2017) - Zhou, M.Z.; Huang, W.M.; Meng, X.L.
Abstract: Almost all previously reported temperature memory effect (TME) in shape memory materials is meant for the heating process. In this paper, we experimentally investigate the TME in the cooling process in a shape memory alloy. Experimental results reveal that the lowest cooling temperature, provided that it is within a temperature range of 15 °C between the original martensite start and finish temperatures, roughly has a linear relationship with the new martensite start temperature in the final cooling process. This finding may be utilized for temperature sensors to estimate the lowest cooling temperature with an accuracy of ± 0.95 °C. Graphical abstract: